Systemic increase in IL-26 is associated with severe COVID-19 and comorbid obstructive lung disease - Cardenas, Eduardo I.; Robertson, Josefina; Misaghian, Salvia; Brown, Jermaine; Wang, Mingyue; Stengelin, Martin; Sigal, George; Wohlstadter, Jacob; Gisslén, Magnus; Lindén, Anders (Frontiers in Immunology, 2024)
Background: IL-26 is a key mediator of pulmonary host defense given its abundant expression in human airways and its established antibacterial properties. Moreover, recent studies indicate that IL-26 can also inhibit viral replication. Along these lines, we have previously reported an increase in the plasma concentration of IL-26 among patients with acute COVID-19 that is linked to harmful hyperinflammation. Nevertheless, it is still unclear whether this systemic increase in IL-26 relates to disease severity, sex, comorbidities, viral load, or the innate immune response in acute COVID-19. Methods: IL-26 was quantified using ELISA in plasma samples from a large cohort of well-characterized patients with acute COVID-19 (n=178) and healthy controls (n=30). The plasma concentrations of SARS-CoV-2 nucleocapsid and spike protein, as well as those of IFN-α2a, IFN-β, and IFN-γ, were determined using electrochemiluminescence immunoassay. The concentration of double-stranded DNA was determined using fluorometry. Results: The plasma concentration of IL-26 was increased in patients with severe/critical COVID-19, particularly among males and patients with comorbid obstructive lung disease. Moreover, the concentration of IL-26 displayed positive correlations with length of hospital stay, as well as with systemic markers of viral load, antiviral immunity, and extracellular DNA. Conclusions: Systemic IL-26 is involved in severe COVID-19, especially in males and patients with comorbid obstructive lung disease. These findings argue that systemic IL-26 has pathogenic and antiviral relevance, as well as biomarker potential.